The Analysis of Flipped Learning Model Based on Geogebra and PBL on Mathematics - Nur Rohman; Budiyono Budiyono; Hasih Pratiwi (BIRCU, 2022)
This research is motivated by the low learning outcomes of students' mathematics with an average national exam of around 55 low, the low learning outcomes are influenced by one of various factors including learning models or methods which sometimes do not support mathematics. Based on this, an alternative learning model is needed to provide understanding both in terms of cognitive and psychomotor. In this case, the geogebra-based flipped learning model helps understand the theory and practice of mathematics. This study aims to determine the regression between flipped learning and problem based learning (PBL) learning models in learning outcomes using geogebra software. This research is in SMPN/SMPT/SMP with the subject of class VIII students. The type of research is an experiment with a 3x3 factorial design with a random sampling technique, each of which is taught using the Flipped learning and problem based learning (PBL) models. Collecting data with tests and questionnaires, while the data analysis technique using inferential analysis of MANOVA and two-way ANOVA through prerequisite, balance, hypothesis and further tests. The conclusion is the knowledge aspect, the GeoGebra flipped learning (FLG) learning model provides better knowledge aspects than the Flipped learning (FL) and problem-based learning (PBL) learning models. The FL learning model provides better knowledge aspects than problem based learning (PBL). Meanwhile, in terms of skills, Flipped learning (FL) learning model provides better skill aspects than problem based learning (PBL); in the aspect of high interpersonal communication knowledge have better knowledge aspects than students with moderate interpersonal communication and low interpersonal communication. Students with moderate interpersonal communication have better aspects of knowledge than students with low interpersonal communication. Meanwhile, in the aspect of skills, students with high interpersonal communication have better skill aspects than students with moderate interpersonal communication and low interpersonal communication. Students with moderate interpersonal communication have better skill aspects than students with low interpersonal communication.